Correlation analysis of blood bicarbonate and short-term adverse prognosis of acute kidney injury - Li Xian; Liu Mei; Pan Ling; Yang Zhen-hua (Linchuang shenzangbing zazhi)
ObjectiveTo evaluate the relationship between serum bicarbonate （HCO3-） concentration and short-term adverse outcomes in acute kidney injury （AKI） patients.MethodsFrom May 2013 to May 2018， clinical data were retrospectively reviewed for 586 hospitalized AKI patients. All-cause mortality within 28 days after a diagnosis of AKI was employed as an endpoint of adverse outcome. According to the concentration of blood HCO3-， they were divided into two groups of HCO3- declining （blood HCO3-< 22.0 mmol/L， n=279） and HCO3- non-declining （blood HCO3-≥22.0 mmol/L， n=307）.ResultsDuring a follow-up period of 28 days， 131 patients （22.4%） died. Kaplan-Meier survival analysis indicated that patients with lower blood HCO3- had a shorter median survival （Log Rank χ2=12.998， P<0.001）. Multivariate COX regression analysis showed that low blood HCO3- was an independent risk factor for 28-day all-cause mortality in AKI patients after adjusting for age， multiple organ dysfunction syndrome （MODS）， cardiac dysfunction， shock and etiology of AKI （HR=0.917， 95%CI 0.885-0.949， P<0.001）. Receiver operating characteristic （ROC） curve analysis indicated that the area under the curve （AUC） of blood HCO3- concentration was 0.703 in predicting 28-day mortality of AKI patients （P<0.001）.ConclusionBlood HCO3- is an important influencing factor of mortality in AKI patients. And lower blood HCO3- has certain clinical value in predicting short-term adverse prognosis of AKI patients.